Studi Ecological Fiscal Transfer sebagai Potensi Pendanaan Lingkungan di Daerah - Haryanto, Joko Tri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2015)
Along with the issue of the increasing prosperity in many parts of the world, including Indonesia, the global development agenda has been shifted from proverty issues to sustainable development goals (Sustainable Development Goalâs or SDGâs) issues. Consecutively, to support this target achievement, the role of the budget becomes very significant, including the Transfer to the Region mechanism. Based on the analysis, the mechanism of the General Allocation Fund (DAU) has the potential to become a source of funding for environmental and ecological forestry. Ecological fiscal transfer mechanism can be manifested through the addition of DAU allocation for the benefit of environmental conservation and forestry. It also can be embodied through the addition of environmental indicators and forestry in existing formulations of DAU.